2020
DOI: 10.1103/physrevfluids.5.074201
|View full text |Cite
|
Sign up to set email alerts
|

Nanodroplets impact on surfaces decorated with ridges

Abstract: This is a repository copy of Nanodroplets impact on surfaces decorated with ridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…It was found that liquid possessed a faster retraction along the ridge than that on the flat surface, leading to a 37% reduction in contact time. 21 Following this work, studies focused on contact time reduction by asymmetric dynamics have been carried out, including the inclined surface, 22,23 curved surface, [24][25][26][27][28][29][30] surfaces with macro structures of different geometries, [31][32][33][34][35][36][37][38][39][40] moving surfaces, 41,42 and off-center impact. 43,44 Besides the aforementioned asymmetric approaches, symmetric bouncing by involving the droplet center to retraction with point-like structure to reduce contact time has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that liquid possessed a faster retraction along the ridge than that on the flat surface, leading to a 37% reduction in contact time. 21 Following this work, studies focused on contact time reduction by asymmetric dynamics have been carried out, including the inclined surface, 22,23 curved surface, [24][25][26][27][28][29][30] surfaces with macro structures of different geometries, [31][32][33][34][35][36][37][38][39][40] moving surfaces, 41,42 and off-center impact. 43,44 Besides the aforementioned asymmetric approaches, symmetric bouncing by involving the droplet center to retraction with point-like structure to reduce contact time has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Nanodroplets have generated a great deal of interest in recent years owing to the rapid development of nanotechnologies such as nanoprinting and nanospray . Recently, complementary to EFD and CFD, molecular dynamics (MD) simulations have been extensively employed to investigate the wetting, spread, rebound, coalescence, etc. of nanodroplets, demonstrating their special abilities in simulating such nanosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the moment with the lowest droplet centroid height can be used as the maximum spreading moment, but we found that this could lead to miscalculation in practice, especially on surfaces with high interaction intensity. Refer to the method of Liu et al, 44 the maximum spreading moment t max is defined as the moment when there are most oxygen atoms under the contact layer and we can get the maximum spreading time τ = t max − t start . The specific solution process is given in Section 1 of the Supporting Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%